The Composition and Phosphorus Cycling Potential of Bacterial Communities Associated With Hyphae of Penicillium in Soil Are Strongly Affected by Soil Origin - Hao, Xiuli; Zhu, Yong-Guan; Nybroe, Ole; Nicolaisen, Mette H. (Frontiers in Microbiology, 2020)
Intimate fungal-bacterial interactions are widespread in nature. However the main drivers for the selection of hyphae-associated bacterial communities and their functional traits in soil systems remain elusive. In the present study, baiting microcosms were used to recover hyphae-associated bacteria from two Penicillium species with different phosphorus-solubilising capacities in five types of soils. Based on amplicon sequencing of 16S rRNA genes, the composition of bacterial communities associated with Penicillium hyphae differed significantly from the soil communities, showing a lower diversity and less variation in taxonomic structure. Furthermore, soil origin had a significant effect on hyphae-associated community composition, whereas the two fungal species used in this study had no significant overall impact on bacterial community structure, despite their different capacities to solubilise phosphorus. However, discriminative taxa and specific OTUs were enriched in hyphae-associated communities of individual Penicillium species indicating that each hyphosphere represented a unique niche for bacterial colonization. Additionally, an increased potential of phosphorus cycling was found in hyphae-associated communities, especially for the gene phnK involved in phosphonate degradation. Altogether it was established that the two Penicillium hyphae represent unique niches in which microbiome assemblage and phosphorus cycling potential are mainly driven by soil origin, with less impact made by fungal identity with a divergent capacity to utilise phosphorus.